American empire : Roosevelt's geographer and the prelude to globalization - Smith, Neil, 1954-2012 (Berkeley : University of California Press, 2003)
The story unfolds through a decisive account of the career of Isaiah Bowman (1878-1950), the most famous American geographer of the twentieth century. For nearly four decades Bowman operated around the vortex of state power, working to bring an American order to the global landscape. An explorer on the famous Machu Picchu expedition of 1911 who came to be known first as "Woodrow Wilson's geographer," and later as Franklin D. Roosevelt's, Bowman was present at the creation of U.S. liberal foreign policy." "A quarter-century later, Bowman was at the center of Roosevelt's State Department, concerned with the disposition of Germany and heightened U.S. access to European colonies; he was described by Dean Acheson as a key "architect of the United Nations." In that period he was a leader in American science, served as president of Johns Hopkins University, and became an early and vociferous cold warrior. A complicated, contradictory, and at times controversial figure who was very much in the public eye, he appeared on the cover of Time magazine." "Bowman's career as a geographer in an era when the value of geography was deeply questioned provides a unique window into the contradictory uses of geographical knowledge in the construction of the American Empire. Smith's historical excavation reveals, in broad strokes yet with lively detail, that today's American-inspired globalization springs not from the 1980s but from two earlier moments in 1919 and 1945, both of which ended in failure. By recharting the geography of this history, Smith brings the politics - and the limits - of contemporary globalization sharply into focus
Arguing that American globalism had a very distinct geography and was pieced together as part of a powerful geographical vision, this text explores US global ambition. The story unfolds through an account of the career of Isaiah Bowman, the most famous American geographer of the 20th century.
Lost geography of the American century -- Part I. From exploration to enterprise: geography on the cusp of empire -- 1898 and the making of a practical man -- "Conditional conquest" : geography, labor, and exploration in South America -- Search for geographical order : the American Geographical Society -- Part II. The rise of foreign policy liberalism: the great war and the new world -- Inquiry : geography and a "scientific peace" -- Last hurrah for Old World geographies : fixing space at the Paris Peace Conference -- "Revolutionarily yours" : the New World, the Council on Foreign Relations, and the making of liberal foreign policy -- Part III. The empire at home: science and politics -- "Geography of internal affairs" : pioneer settlement as national economic development -- Kantian university : science and nation building at Johns Hopkins -- Part IV. The American lebensraum -- Geopolitics : the reassertion of Old World geographies -- Silence and refusal : refugees, race, and economic development -- Settling affairs with the Old World : dismembering Germany? -- Toward development : shaking loose the colonies -- Frustrated globalism, compromise geographies: designing the United Nations -- Part V. The bitter end -- Defeat from the jaws of victory -- Geographical solicitude, vital anomaly.
Includes bibliographical references (pages 465-537).
Print version record.
eBooks on EBSCOhost
Keywords: Bowman, Isaiah, -- 1878-1950.; Bowman, Isaiah, -- 1878-1950; Geographers -- United States -- Biography; Geography -- United States -- History -- 20th century; Globalization -- History -- 20th century; Géographie -- États-Unis -- Histoire -- 20e siècle.; Mondialisation -- Histoire -- 20e siècle.; TRAVEL -- Museums, Tours, Points of Interest; BIOGRAPHY & AUTOBIOGRAPHY -- Adventurers & Explorers; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; TRAVEL -- Hikes & Walks; TRAVEL -- Budget; TRAVEL -- Special Interest -- Ecotourism; TRAVEL -- Parks & Campgrounds; TRAVEL -- Reference; TRAVEL -- Road Travel; TRAVEL -- Special Interest -- Adventure; HISTORY -- United States -- General; Geographers; Geography; Globalization; United States; 1900-1999; american empire; american history; colonialism; colonies; contemporary; cultural history; cultural studies; culture; debunked; empire; europe; european colonialism; european colonies; european history; explorer; foreign policy; geography; global; globalism; globalization; international; modern world; myth; power structure; power struggle; science; social history; social studies; state department; united nations; united states history; us history; collective biographies; Biographies; History; Biographies; Biographies